Spatial Validation Analysis And Prediction Of Service Reach Of Trans Banyumas Purwokerto-Banyumas Corridor 4 Ahead Of Operation In January 2026 - Dendi Putra Prakoso; Purwadi Purwadi (International Journal of Health Engineering and Technology, 2026)
The expansion of Trans Banyumas services through Corridor 4 to the Banyumas area has entered the final stage with an operational schedule set for January 1, 2026. This study conducted a pre-operational evaluation to validate route readiness and predict service coverage using Geographic Information Systems (GIS). By modeling the route along the Bulupitu Purwokerto Terminal to Banyumas Terminal which includes 49 Bus Stops (TPB), the analysis used QGIS 3.40.11 with Network Analysis and Service Area Analysis methods. The results show that the route has high efficiency with an estimated travel time of 45-60 minutes. Service Area analysis with a radius of 400 meters confirmed that the TPB is able to cover 6 major hospitals, 8 educational institutions, and all major tourist destinations in the Old Town of Banyumas. Spatial validation concluded that the route is very feasible for operation, with high potential to support the revitalization of heritage areas and the integration of public transportation in the Greater Banyumas area